Justification of the program therapy of acute hepatitis C - E. A. Mikhailova; O. L. Sobolevskaya (Журнал инфектологии)
Treatment of acute hepatitis C remains one of the main problems of modern hepatology. There are many variants of treatment, but there is no common opinion about scheme and time of onset of the therapy. From the other hand, early treatment can prevent chronisation in more than 70% of cases. Specific therapy was used 135 patients with acute hepatitis C aged from 16 to 52 years (26,5+0,7 years). Our analysis has shown, that its better to start specific therapy on the second month of the disease with -interferon monotherapy by induction scheme.